Profit and Risk for Property Business Using Sharia and Conventional System: A Comparative Analysis - Zaini Muchlis; Ayif Fathurrahman (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2021)
Sharia and conventional business management system are often become a parameter in gaining profit and managing the risk faced by the entrepreneurs. This research aims to determine the comparison of profit and risk obtained by the property entrepreneurs in conducting their business when they use conventional or sharia system. This research is qualitative descriptive analysis. The variables that would be investigated are the profit obtained by the property business owner and the risks in conducting this business when the business owner uses sharia and conventional system in the capital investment or the buying and selling process of a certain property unit. The data was collected through an interview and documents. The article shows that conventional and sharia are a concept or system that generally used by the entrepreneurs in conducting their business to obtain the profit and face the risks. Both of the systems have advantages and disadvantages. This article further argues that sharia system gives a higher profit and fewer risks rather than the conventional system. It is because in the sharia system, entrepreneurs or costumers are not concerned about the burden of the interest and fines of the debt from a financing institution. Although there are risks considered such as bad credit and longtime cash flow, the profit obtained through the sharia system is higher than the conventional one.